Organisational learning in professional discourses. - Martin Sedláček; Petr Novotný; Lenka Hloušková; Milan Pol; Bohumíra Lazarová (Czech Pedagogical Society, 2012)
Authors of the paper discuss the concept of organisational learning. Theyrefer to a wide range of definitions and concepts, point out some differences from related or analogous concepts used, such as knowledge management and learning organisation. They note the discussions that relate to key topics. These discussions concern levels at which organisational learning can take place, the effect on behaviour organisational performance. The following section of this article presents organisational learning as a process and describes the stages of organisational learning. The purpose of the article is to provide an overview of efforts to define organisational learning, including criticism of the results of this effort. The last partis devoted to selected theories and empirical findings on organisational learning atschool. The authors stress the importance of organisational learning for schools asspecific organisations and express request to examine the processes of organisational learning in this context.